2013
DOI: 10.5664/jcsm.2668
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Step Pathway Connecting Short Sleep Duration to Daytime Somnolence, Reduced Attention, and Poor Academic Performance: An Exploratory Cross-Sectional Study in Teenagers

Abstract: Pediatric Daytime Sleepiness Scale (PDSS), we found that somnolence was independently and signifi cantly related to poor grades in language or math after adjusting for age, gender, body mass index (BMI), and the presence of snoring or apneas.2 Daytime somnolence in sleep deprived children may lead to reduced attention, causing impaired learning and academic failure.10 background: A multi-step causality pathway connecting short sleep duration to daytime somnolence and sleepiness leading to reduced attention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 31 publications
(32 reference statements)
4
48
2
4
Order By: Relevance
“…Recent studies have reported that short sleep duration (< 9 h for adolescents) affects academic achievement, motivation and attention (Merikanto et al, 2013;Perez-Lloret, 2013;Stea et al, 2014). Results obtained in the present study indicated that time in bed on weekdays was positively related to GPA.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies have reported that short sleep duration (< 9 h for adolescents) affects academic achievement, motivation and attention (Merikanto et al, 2013;Perez-Lloret, 2013;Stea et al, 2014). Results obtained in the present study indicated that time in bed on weekdays was positively related to GPA.…”
Section: Discussionsupporting
confidence: 73%
“…24 On the contrary, sleep duration and subjective sleepiness did not correlate with academic performance. Several studies have associated academic performance and short sleep duration 25 or subjective sleepiness 26 in adolescents, whereas other studies failed to detect these relationships. 3,27 These discrepancies may be due to the diverse causes of short sleep duration and the inaccuracies associated with subjective measurements of sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Moreover, congruent findings of decreased sleep duration associated with poor examination performance were found in Gruber et al's study on children's performance on IQ measures and Perez-Lloret et al's study on adolescents' performance on mathematics and literature coursework. [12][13] The causal relationship between sleep duration (cause) and academic performance (outcome) cannot be established because of the nature of the cross-sectional study. One may argue that students who performed well in class slept longer the night prior to an examination because they were more prepared, hence did not feel they needed additional time to study.…”
Section: Discussionmentioning
confidence: 99%